2019
DOI: 10.3390/ma12091483
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Refractive Index on Antireflectance Efficiency of Thin Films

Abstract: In today’s world, scientific development is tremendously strengthened by imitating natural processes. This development remarkably validates progressive and efficient operation of multifunctional thin films in variable ecological circumstances. We use TFCalc thinfilm software, a reliable and trustworthy simulation tool, to design antireflective (AR) coatings for solar cells that can operate in varying environmental conditions and can be functional according to user-defined conditions. Silicon nearly reflects 36… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 27 publications
0
21
0
Order By: Relevance
“…The disordered nanotextured carbon materials have broad absorption properties over the entire range from mid-IR to UV, as shown in [44]. Zeolite 3A-carbon layers evidenced a marked enhancement of the broadband absorption [21]. The extinction spectra for zeolite 3A-carbon coatings are characterized the sum of value absorbed and scattered light [25], as showed in Figure 4b.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The disordered nanotextured carbon materials have broad absorption properties over the entire range from mid-IR to UV, as shown in [44]. Zeolite 3A-carbon layers evidenced a marked enhancement of the broadband absorption [21]. The extinction spectra for zeolite 3A-carbon coatings are characterized the sum of value absorbed and scattered light [25], as showed in Figure 4b.…”
Section: Resultsmentioning
confidence: 99%
“…In order to achieve broadband AR coatings for solar cells, a straightforward and scalable process is desirable [21,22,23,24]. Thus, the proposed deposition technique is highly promising because of easy transferal to mass production, cost-effectiveness, and compatibility with integrated circuit technology.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, a coating system that has the capability to enhance the transmission energy both at 1053 and 527 nm was needed. Theoretical calculations from optical design software TFCalc TM [32][33][34] showed that the polysiloxane coating with RI around 1.37 and thickness about 131nm, accompanied with an AR coating whose RI was about 1.23 and thickness around 144nm, could achieve ultrahigh transmission at 1053 nm (>99.5%) and 527 nm (>99.5%), simultaneously (shown in Figure 6b). Optimized from the previous work in this study, a polysiloxane coating with an MSN embedding proportion of 3 was fabricated under the spin velocity of 650 rpm and time of 20 s. The RI and thickness of such coating were measured to be 1.368 and 132 nm after UV curing, respectively.…”
Section: Coating Applicationmentioning
confidence: 99%
“…7a). 50,51 In other words, beside the high haze effect, the gradual change of the refractive index by silk broin helps to improve the photodiode efficiency as well.…”
Section: Applications In Silicon Photodiodesmentioning
confidence: 99%